Controlling a Master Switch of adipocyte development and insulin sensitivity: Covalent Modifications of PPARγ - Floyd, Z. Elizabeth (2012)
Adipocytes are highly specialized cells that play a central role in lipid homeostasis and the maintenance of energy balance. Obesity, an excessive accumulation of adipose tissue, is a major risk factor for the development of Type 2 diabetes mellitus (T2DM), cardiovascular disease, and hypertension. A variety of studies suggest that obesity and T2DM can be linked to a breakdown in the regulatory mechanisms that control the expression and transcriptional activity of PPARγ. PPARγ is a nuclear hormone receptor that functions as a master switch in controlling adipocyte differentiation and development. Also important in controlling glucose homeostasis and insulin sensitivity, PPARγ is a ligand-dependent transcription factor that is the functional receptor for the anti-diabetic thiazolidinediones (TZDs). In the last fifteen years, a variety of covalent modifications of PPARγ activity have been identified and studied. These covalent modifications include phosphorylation, ubiquitylation, O-GlcNAcylation and SUMOylation. Covalent modifications of PPARγ represent key regulatory mechanisms that control both PPARγ protein stability and transcriptional activity. A variety of PPARγ transgenic models, including mice heterozygous for PPARγ, have demonstrated the importance of PPARγ expression in glucose homeostasis and insulin resistance. In the following review, we have highlighted the regulation of PPARγ by covalent modifications, the interplay between these interactions and how these post-translational modifications impact metabolic disease states.